Sedentary time and physical activity exposure patterns and musculoskeletal symptoms of Australian office workers - Parry, Sharon (Curtin University, 2014)
Excessive sedentary behaviour is associated with increased risk of many cardio-metabolic disorders. This thesis described the amount and pattern of sedentary time, light activity and MVPA of office workers at work and during non-work periods. Further, this thesis determined whether workplace interventions could modify the amount and pattern of accumulation of sedentary time, light activity and MVPA of office workers at work and during non-work periods.